EDUKASI PEMAKAIAN MASKER SEBAGAI UPAYA PENEGAKAN PROTOKOL KESEHATAN DI ERA PANDEMI COVID -19 PADA MASYARAKAT KAMPUNG KEBONSO RT 02 RW 02, PULISEN, BOYOLALI - ABDUL ROHIM; ADHIPUTRO PANGARSO WICAKSONO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
The spread of Covid-19 has caught the attention of both the public and the government. With the increasing rate of spread, the government is more responsive and issues various policies. One of the policies to slow down the spread of Covid-19 by taking into account the pace of the economy is the application of a new life order or often called the New Normal. The new life order (New Normal) demands that people always wear masks and pay attention to their health. The existence of this policy makes all people need to know the importance of using masks and living healthily. Therefore, there is a need for Covid-19 education efforts and the use of masks to slow the spread of Covid-19. This education uses several modes, including: the virtual media method and the lecture method. Evaluation related to this activity uses a questionnaire to find out how effective Covid-19 education and mask donations are to slow the spread rate. This educational activity is targeted at village people who, in fact, do not understand Covid-19 information. The results of the activity showed that the covid-19 education and distribution of masks provided by the facilitators could increase the awareness of the village community and be useful for the rate of spread of Covid-19 in the area.